Depigmentation - Kim, Tae-Heung; Kim, Tae-Heung (IntechOpen, 2019)
Depigmentation, lightening of the skin and mucosa, can be caused by local or systemic conditions, and there may be partial or complete loss of pigment. Although depigmented patches may not matter in Caucasians, it is very serious for pigmented skin.Depigmentation can also be a therapeutic goal for cosmetic treatment. Many vitiligo patients who received depigmentation treatment experienced paradoxical jealousy because of their clean white skin. To improve facial blemishes, many people spend their money on laser, chemical peel, and cosmetic treatments. In this book, we focus on two opposite sides of depigmentation: diseases of depigmentation and therapeutic depigmentation presented by global experts.
English
Keywords: Dermatology; Dermatology